2023
DOI: 10.1101/2023.08.09.552643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced Deep Convolutional Neural Network for SARS-CoV-2 Variants Classification

Abstract: High-throughput sequencing techniques and sequence analysis have enabled the taxonomic classification of pathogens present in clinical samples. Sequencing provides an unbiased identification and systematic classification of pathogens and this is generally achieved by comparing novel sequences to pre-existing annotated reference databases. However, this approach is limited by large-scale reference databases which require considerable computational resources and skills to compare against. Alternative robust meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…(2023) applied computational methods for identifying potential inhibitors targeting cdk1 in colorectal cancer, showcasing the integration of genomics and computational approaches in cancer research. In the realm of infectious diseases, Mwanga et al . (2023) developed an enhanced deep convolutional neural network for SARS-CoV-2 variants classification, highlighting the pivotal role of artificial intelligence in understanding and combating emerging viral strains.…”
Section: Introductionmentioning
confidence: 99%
“…(2023) applied computational methods for identifying potential inhibitors targeting cdk1 in colorectal cancer, showcasing the integration of genomics and computational approaches in cancer research. In the realm of infectious diseases, Mwanga et al . (2023) developed an enhanced deep convolutional neural network for SARS-CoV-2 variants classification, highlighting the pivotal role of artificial intelligence in understanding and combating emerging viral strains.…”
Section: Introductionmentioning
confidence: 99%
“…This is closely followed by Europe (9.6% of the world population) with 36.7% of cases and 28.7% of global cases and deaths respectively (2,374 deaths/million). Study reports have shown that next-generation sequences can be used to screen for disorders in newborns [9], for the study of pathogen evolution using African SARS-CoV-2 sequences [18], prostate cancer biomarker discovery [10], malaria/CoVID-19 biomarker discovery [58], SARS-CoV-2 variants classification [59], HIV-1 evolution in sub-Saharan Africa [60], analysis of RNA-seq and ChIP-seq data [61], and ebola virus comparative genomics [62]. We will be using next-generation sequencing data for our investigation in this study.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs have now been suggested for clinical diagnosis for a variety of disorders due to their serum stability, affordability, speed, and non-invasive qualities [15]. In the future, genomic medicine would rely largely on our ability to use sequencing data for clinical applications like biomarker discovery, viral pathogen evolution [16], SARS-CoV-2 variants classification [17], for other applications like screening for disorders in newborns [18], HIV-1 evolution in sub-Saharan Africa [78], prostate cancer biomarker discovery [79], malaria/CoVID-19 biomarker discovery [80], Chromatin Immunoprecipitation [81], and viral comparative genomics [82].…”
Section: Introductionmentioning
confidence: 99%